The Relationship Between Perceived Usefulness, User-Friendliness, Risk Perception and Technology Acceptance on Purchase Intentions - Darlina, Darus (2024)
This study investigates the influence of Artificial Intelligence (AI) on consumer behaviour within Malaysia's online retail industry. Understanding how AI-related factors affect purchase intentions is crucial for retailers aiming to capitalize on technological advancements as the digital marketplace evolves. The study's objectives were to examine the roles of perceived ease of use, perceived usefulness, AI performance risk, and technology acceptance in shaping attitudes towards AI and to determine how these attitudes influence purchase intentions. The problem statement addresses the gap in existing literature regarding the impact of AI on consumer purchase behaviour, particularly within the context of an emerging digital economy like Malaysia's. With online retail rapidly integrating AI, there is a pressing need to understand the implications of this integration from a consumer perspective. A quantitative research methodology was employed, utilizing a survey distributed to a diverse group of Malaysian online retail consumers. Statistical analysis, including regression and correlation, was utilized to interpret the data, offering a robust examination of the relationships between the variables of interest. The financial analysis component aimed to correlate consumer attitudes towards AI with purchase behaviours to provide insights into potential revenue implications for online retail businesses. It explored the willingness of consumers to engage financially with AI-enhanced platforms and the likelihood of AI adoption influencing shopping frequency and expenditure. The study concluded that perceived usefulness and ease of use significantly impact consumer attitudes towards AI, influencing purchase intentions. AI performance risk was also positively correlated with purchase intentions, suggesting a complex relationship where perceived risks may drive consumer engagement under certain conditions. Based on these findings, the study recommends that online retailers in Malaysia focus on improving AI functionalities that enhance user experience, address AI performance risks transparently, and foster technology acceptance to optimize the benefits of AI in e-commerce. Overall, the study provides valuable insights into consumer AI acceptance. It offers a foundation for online retailers to develop strategies that align with consumer preferences and enhance their competitive edge in the digital marketplace.